ChemInform Abstract: Room‐Temperature Base‐Free Copper‐Catalyzed Trifluoromethylation of Organotrifluoroborates to Trifluoromethylarenes. Issue 14 (20th March 2013) - Huang, Yuanyuan; Fang, Xin; Lin, Xiaoxi; Li, Huaifeng; He, Weiming; Huang, Kuo‐Wei; Yuan, Yaofeng; Weng, Zhiqiang
Abstract This reaction runs in the absence of any additional base or oxidant and tolerates a variety of functionalities.